Exosomes in the Thymus: Antigen Transfer and Vesicles - Skogberg, Gabriel; Telemo, Esbjörn; Ekwall, Olov (Frontiers in Immunology, 2015)
Thymocytes go through several steps of maturation and selection in the thymus in order to form a functional pool of effector T-cells and regulatory T-cells in the periphery. Close interactions between thymocytes, thymic epithelial cells, and dendritic cells are of vital importance for the maturation, selection, and lineage decision of the thymocytes. One important question that is still unanswered is how a relatively small epithelial cell population can present a vast array of self-antigens to the manifold larger population of developing thymocytes in this selection process. Here, we review and discuss the literature concerning antigen transfer from epithelial cells with a focus on exosomes. Exosomes are nano-sized vesicles released from a cell into the extracellular space. These vesicles can carry proteins, microRNAs, and mRNAs between cells and are thus able to participate in intercellular communication. Exosomes have been shown to be produced by thymic epithelial cells and to carry tissue-restricted antigens and MHC molecules, which may enable them to participate in the thymocyte selection process.